Neutrophil Heterogeneity in Wound Healing - Filippo Renò; Corinna Anais Pagano; Monica Bignotto; Maurizio Sabbatini (Biomedicines)
Neutrophils are the most abundant type of immune cells and also the most underestimated cell defenders in the human body. In fact, their lifespan has also been extensively revised in recent years, going from a half-life of 8–10 h to a longer lifespan of up to 5.4 days in humans; it has been discovered that their mechanisms of defense are multiple and finely modulated, and it has been suggested that the heterogeneity of neutrophils occurs as well as in other immune cells. Neutrophils also play a critical role in the wound healing process, and their involvement is not limited to the initial stages of defense against pathogens, but extends to the inflammatory phase of tissue reconstruction. Neutrophil heterogeneity has recently been reported at the presence of distinct subtypes expressing different functional states, which contribute uniquely to the different phases of innate immunity and wound healing. This heterogeneity can be induced by the local microenvironment, by the presence of specific cytokines and by the type of injury. The different functional states of neutrophils enable a finely tuned response to injury and stress, which is essential for effective healing. Understanding the functional heterogeneity of neutrophils in wound healing can unveil potential pathological profiles and therapeutic targets. Moreover, the understanding of neutrophil heterogeneity dynamics could help in designing strategies to manage excessive inflammation or impaired healing processes. This review highlights the complexity of neutrophil heterogeneity and its critical roles throughout the phases of wound healing.